Supplemental oxygen therapy in COVID-19 - Smit, FE; Oelofse, AN; Linegar, AL; Botes, L; Turton, EW (SA Heart Journal, 2020)
South Africa face a significant shortage of ventilator-supported intensive care (ICU) beds during the peak phase of the COVID-19 pandemic, further exacerbated by severe ICU-staff shortages. It is also recognised that the mortality rate for ventilated patients might be as high as 88%. In the absence of a vaccine and proven effective pharmacotherapy, it is important to understand the pathophysiological processes causing progression. Early type-L COVID-19, associated with pulmonary thrombo-embolism, may be amenable to treatment with careful anti-coagulation and supplementary oxygenation strategies. This could attenuate the severe hyperventilation phase causing patient self-inflicted lung injury (P-SILI) that contributes to the development of type-H COVID-19 pneumonia. Type-H is an ARDS variant requiring intubation and ventilation and is associated with a very high mortality rate. Stepwise non-invasive positive pressure ventilation strategies (NIPPV) providing supplementary oxygen have shown benefit and, in the South African context, may be the only realistic strategy to deal with high numbers of patients during the early type-L phase of the disease. To address this, a mobile wall unit has been created that allows for stepwise supplementary oxygen therapy according to protocol – including NIPPV as well as standard ventilation. The unit can support modified wards, field hospitals or high care areas in existing facilities. It allows for NIPPV support within a hood system linked to scavenger lines addressing aerolisation. Standard humidification, flow regulators, vacuum systems, HFNC and CPAP systems, as well as monitoring equipment that are readily available in South Africa, can be linked to the system addressing availability issues.